A Chapter of Theology of Grace. The Salvation of the Gentiles or Unbelievers. Reflections of a Young French Missionary in the Argentine Pampas. Jorge María Salvaire, CM, and the Indian Chief José María Railef (1874) - Durán, Juan Guillermo (Teología, 2016)
The author recreates in these pages the meeting of the young French priest Jorge María Salvaire (cm) with the Araucanian Cacique José María Railef in 1874 during the mission in the “toldería” (indigenous camp) of the “La Barrancosa” lagoon, in the area of the current city of Bragado (province of Buenos Aires). The old cacique, a revered and respected man, to whom Salvaire had a particular affection since the day he met him, decided with remarkable courage to undertake the journey that would bring him to receive the sacraments of Christian initiation. Indeed, the moral silhouette of the catechumen motivated in the missionary a series of interesting reflections on the problem of salvation of the gentiles or non-believers based on the New Testament, the patristic tradition and Saint Thomas Aquinas.